Evaluation of intraocular pressure estimates obtained using an iCare rebound tonometer. (4th October 2016) - Khanal, Safal; Walton, Meredith; Davey, Pinakin Gunvant
Abstract : Background: The aims of this study were to evaluate the intra‐ and inter‐observer repeatability of intraocular pressure (IOP) estimates obtained using an iCare rebound tonometer and to investigate the variation in IOP measurements due to positional differences in probe placement on the cornea. Methods: The IOP estimates were obtained by two observers, twice on one eye, of 114 subjects using an iCare tonometer on the central cornea. Additionally, IOP and corneal thickness were measured in 38 subjects at three locations, namely, central, at 1.5 mm nasally and at 1.5 mm temporally from the central cornea. Agreement among measurements was assessed using Bland and Altman plots and the difference in measurements obtained by the observers was compared using paired t‐test. Values obtained from central, nasal and temporal regions were compared using one‐way analysis of variance. Results: The mean IOP measurements obtained by observer 1 on two attempts were 16.2 and 16.0 mmHg (p > 0.05) were significantly different from the IOP values obtained by observer 2 on two occasions (16.3 and 15.7 mmHg; p < 0.0001). The limits of agreement (LOA) of intra‐observer repeatability were −2.9 to +2.6 mmHg and −3.4 to +2.2 for observers 1 and 2, respectively. The LOA of inter‐observer repeatability for first and second sequences were −2.8 to +3.0 mmHg and −3.3 to +2.7 mmHg with the second sequence of measurements being significantly different (p = 0.03). Although the corneal thickness was significantly greater nasally and temporally, when compared to the central location, by 32 and 20 microns respectively (p < 0.0001), the measured IOPs on those locations were not significantly different, when compared to the central measurements (p = 0.14). Conclusion: There is good intra‐ and inter‐observer repeatability of IOP data, as obtained by the iCare rebound tonometer, although the results may be slightly influenced by practitioner experience. The difference in IOP estimates obtained by different observers is unlikely to be of clinical significance. Corneal thickness showed regional variation; however, this did not influence IOP measurements obtained from those locations.